2007
DOI: 10.1128/aac.00853-06
|View full text |Cite
|
Sign up to set email alerts
|

Development and Characterization of a Novel Single-Cycle Recombinant-Virus Assay To Determine Human Immunodeficiency Virus Type 1 Coreceptor Tropism

Abstract: Most human immunodeficiency virus type 1 (HIV-1) strains require either the CXCR4 or CCR5 chemokine receptor to efficiently enter cells. Blocking viral binding to these coreceptors is an attractive therapeutic target. Currently, several coreceptor antagonists are being evaluated in clinical trials that require characterization of coreceptor tropism for enrollment. In this report, we describe the development of an automated and accurate procedure for determining HIV-1 coreceptor tropism (Trofile) and its valida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
280
0
9

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 316 publications
(293 citation statements)
references
References 44 publications
(46 reference statements)
4
280
0
9
Order By: Relevance
“…Among phenotypic assays, Trofile test has been the most widely used (as discussed by Whitcomb et al [8]), and it has been recently replaced by an equivalent with enhanced sensitivity (Trofile ES or ESTA) (as discussed by Trinh et al [9]). This strategy utilizes patient-derived env gene amplified by PCR and inserted into an expression vector.…”
Section: Methodsmentioning
confidence: 99%
“…Among phenotypic assays, Trofile test has been the most widely used (as discussed by Whitcomb et al [8]), and it has been recently replaced by an equivalent with enhanced sensitivity (Trofile ES or ESTA) (as discussed by Trinh et al [9]). This strategy utilizes patient-derived env gene amplified by PCR and inserted into an expression vector.…”
Section: Methodsmentioning
confidence: 99%
“…As a result, a number of subjects were misjudged to have R5 virus at screening, whereas they actually harbored Dual/Mixed (D/M) virus populations when they entered clinical trials of CCR5 inhibitors; these patients appeared to have a blunted virologic response and high rates of early virologic failure [152][153][154]. Application of an enhanced-sensitivity Trofile assay or "deep sequencing" and re-analysis of the data showed that virologic failure in a significant proportion of these patients stemmed from the expansion of pre-existing minority CXCR4-using variants that went undetected during the first round of testing [155][156][157]. Accurate determination of coreceptor usage is therefore necessary to optimize treatment strategies before the initiation of and during therapy with CCR5 inhibitors.…”
Section: In Vivo Resistance: Potential Expansion Of Pre-existing CXCmentioning
confidence: 99%
“…The Trophile ES assay (Monogram Biosciences) tests for CCR5 coreceptor trophism but requires a viral load of preferably greater than 1,000 copies/ml [44]. The newer Trophile DNA assay (Monogram Biosciences) however, may be used even if the viral load is undetectable, such as the case of a patient receiving an optimal drug regimen but needing to be switched because of an adverse drug effect.…”
Section: Resistance Testsmentioning
confidence: 99%